Social study on factors associated with the early diagnosis of lip cancer in the population of Camagüey - Yanelis Suarez Conde; Guillermo de la Cruz García (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
The work constitutes an analysis of the different factors that interfere in the early diagnosis of lip cancer in the population of Camagüey. A descriptive and cross-sectional study was carried out, from the perspective of the Science, Technology and Society approach, which included all patients diagnosed with the disease in the period from January 2015 to December 2020.The socio-environmental factors that play the most important role in the origin of lip neoplasms that can be modified from the community are described.